ETHNO-RELIGIOUS CONFLICT AND SETTLEMENT DYNAMICS IN PLATEAU STATE, NIGERIA, 1994-2012 (2016)
Persistent communal conflicts in Plateau State underscore the differences between ethno-religious identities and aggravated segregation in human settlements. Existing studies on ethno-religious conflict have focused on colonial segregated settlement policy otherwise known as the Sabon Gari. These studies have neglected settlement dynamics as both cause and effect of ethno-religious conflicts. This study, therefore, interrogated the complex interaction between ethno-religious conflict and settlement dynamics in Plateau State. This is with a view to showing how conflicts structure and restructure settlements and their implications for inter-group relations, group mobilisation and infrastructural development. The study adopted Lawler’s Relational theory and case study research design. Respondents were purposively selected from four Local Government Areas comprising Jos North, Jos South, Barkin-Ladi and Riyom. Primary data were collected through 46 in-depth interviews from twelve neighbourhood leaders, eleven ethno-religious group leaders, three members of civil society organisations, four estate managers, two security officials, two academics and twelve youth leaders. A total of six Focus Group Discussions were held: one each with Afizere, Anaguta and Hausa ethnic groups in Jos North, Berom in Jos South, Igbo in Barkin-Ladi and Fulani in Riyom. Non-participant observation method was also employed. Historical documents from National Archives, Kaduna were sourced and utilised. Secondary data consisted of Government white papers, gazettes, reports, petitions, books and journal articles. Data were content and thematically analysed. In the historical evolution of Plateau State, the climate as well as inter-group relations played significant roles in the settlement dynamics. In pre-colonial Plateau State people lived on top of mountains for fear of being attacked by foreign elements. Colonial Plateau State experienced relative peace. Nevertheless, the colonialists divided the area into Native Town and Township which facilitated forms of identity conflicts. Before 1994, different groups lived together without considering ethno-religious identities. However, persistent violence between ethno-religious groups since 2001 led to the emergence of exclusive neighbourhoods for Christians (AngwanRukuba, Gyel, Kashan-Gwol, and Shonong) and Muslims (Gangare, Kasali, AngwanSarki and Gashish). This trend deepened in rural areas from 2012 as conflicts intensified. The emerging settlement dynamic has created atmosphere of fear, giving rise to ethno-religious insecurity, impacted trust and created a culture of violence. It has also facilitated group mobilisation for violence by aiding the drive to safeguard the emerging settlements. Groups build worship centres and community halls within the new settlements and these structures have reinforced group mobilisation and bind their capability and legitimacy for conflicts. This has affected infrastructural development; certain neighbourhoods have been totally neglected while the exclusion narrative in the area has further intensified violence. Settlement dynamics are central to ethno-religious conflict because of their identity and security implications. Group segregation in settlements is a security threat and conflict factor. To mitigate conflicts and promote inter-group peaceful relations, it is imperative to develop in neighbourhoods, structures of inter-group relations like sports complexes and town halls. Faith based organisations should be monitored to limit radicalised views. Government and philanthropists need to collaborate to rebuild destroyed homes and facilitate people’s return after conflicts